Evaluation of an Education Program on Community Orientation among Community Health Nurses in Fiji - Sachiko Tanabe; Kayoko Hirano; Satoko Yanagisawa; Silina Waqa Ledua; Mereani Tukana (Nursing Open, 2023)
Abstract Aim The study objective was to evaluate the effectiveness of an education program to improve community orientation among community health nurses in Fiji. A 1.5‐day education program was developed that enabled participants to learn a concept through discussion, as they reviewed their experiences. Design This study used mixed methods research. Methods The education program involving 78 community health nurses and supervisors was conducted. The 30‐item Community Orientation among Community Health Nurses scale, six‐item program evaluation questionnaire, and participant reflection sheets were analyzed using both quantitative and qualitative methods. Results Program evaluations demonstrated high satisfaction among participants. The content analysis of participant views on community orientation revealed three categories; utilizing community intelligence in community activities, relationships with community members as a community health nurses, and human resource development tool. Our findings suggest that this education program should be held regularly, in conjunction with on‐the‐job and off‐site training.